4-V flexible all-solid-state lithium polymer batteries. (October 2019) - Chen, Zhen; Kim, Guk-Tae; Wang, Zeli; Bresser, Dominic; Qin, Bingsheng; Geiger, Dorin; Kaiser, Ute; Wang, Xuesen; Shen, Ze Xiang; Passerini, Stefano
Abstract: Lithium metal polymer batteries have attracted extensive interest spurred by the pursuit of high safety as well as high-energy power sources. In this work, we report, a flexible, all-solid-state lithium metal polymer battery composed of the 4V-class, LiNi1-x Co0.2 Mnx O2 cathode, lithium anode and PEO10 -LiTFSI-PYR14 TFSI2 ternary solid polymer electrolyte. Compared with LiNi0.4 Co0.2 Mn0.4 O2, the Ni-rich LiNi0.6 Co0.2 Mn0.2 O2 cathode composite showed considerably more stable cycling performance and C-rate capability, as a result of the more homogeneous particle distribution that provides better electronic and ionic conductivity, and, most important, more stable interfacial impedance with smaller values upon cycling resulting from the formation of quickly stabilized SEI and the significantly alleviated phase transitions. Through the systematic investigation, this work herein provides a valid assessment of the potential use of 4V-class Ni-rich NCM for practical lithium metal polymer batteries. Graphical abstract: A flexible, all-solid-state lithium metal polymer cell, comprising of Ni-rich NCM, PEO-based ternary polymer electrolyte and Li metal is presented, which exhibit superior electrochemical performance.Image 1 Highlights: Solvent-free polymer electrolyte operating at room temperature. Polymer electrolytes enable the realization of all-solid-state, but flexible lithium metal cells. Lithium metal polymer cell offer high flexibility and resilience to mechanical damages. High voltage positive electrodes/polymer electrolytes interfaces and interphases.